Anisotropic single-variant of (Mn54Al46)97C3. (15th January 2018) - Zhang, Chi; Zhang, Tianli; Wang, Jingmin; Zhao, Shuang; Wu, Yuye; Jiang, Chengbao
Abstract: The Mn-Al permanent magnet is considered as a candidate to fill the gap between the best ferrite and Nd–Fe–B magnets. Anisotropy is hard to be obtained due to the formation of randomly oriented multi-variants of the ferromagnetic τ-phase. In this work, an anisotropic single-variant is achieved through constrained martensitic transformation of the (Mn54 Al46 )97 C3 single crystal, which is based on the principle of magnetoelastic energy. This work guides a new approach for developing anisotropic Mn-Al permanent magnets. Graphical abstract: Image 1